2003
DOI: 10.1093/her/cyf030
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' attitudes and self-perceptions about anti-tobacco advocacy

Abstract: Communities are organizing into coalitions with the goal of reducing tobacco use, particularly among youth. Adolescents could make effective and persuasive anti-tobacco advocates in their respective communities, but their attitudes about tobacco advocacy and their perceptions of their own abilities as advocates are unknown. Therefore, the present project assessed attitudes and self-perceptions about anti-tobacco advocacy in 159 high school students attending a tobacco advocacy conference. After the meeting, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…It is not surprising, therefore, that girls scored better in terms of their behavioral intentions, attitudes toward tobacco, and beliefs about peers and tobacco. This sex difference is consistent with research showing that southern teenage girls have more positive attitudes than boys toward anti-tobacco advocacy [12]. However, it is inconsistent with the national averages, in which girls and boys are about the same [2], or with Connecticut public and private school students in 1988-1996, where girls in grades 10-12 are more likely to smoke than boys [13].…”
Section: Discussionsupporting
confidence: 76%
“…It is not surprising, therefore, that girls scored better in terms of their behavioral intentions, attitudes toward tobacco, and beliefs about peers and tobacco. This sex difference is consistent with research showing that southern teenage girls have more positive attitudes than boys toward anti-tobacco advocacy [12]. However, it is inconsistent with the national averages, in which girls and boys are about the same [2], or with Connecticut public and private school students in 1988-1996, where girls in grades 10-12 are more likely to smoke than boys [13].…”
Section: Discussionsupporting
confidence: 76%
“…Common reasons people give for not being involved in advocacy include perceptions that they do not have the time or the skills and do not know where to begin (Galer‐Unti, Tappe & Lachenmayr, 2004). Carver, Reinert, Range, & Campbell (2003) reported that some youth may lack confidence in their ability to participate in activism.…”
Section: Youth and Advocacymentioning
confidence: 99%
“…Two behavioral intentions scales included items about intentions to avoid and ask others to avoid tobacco, or to benefit from tobacco companies/products. Behavioral Intentions [16] was 10 items about tobacco-related intentions (i.e., "If a friend offered me a cigarette, I would say no"), with high scores indicating intent to avoid tobacco. Note that in Carver et al [16], seven items involved asking others to refrain from using tobacco.…”
Section: Methodsmentioning
confidence: 99%